INFLUENCE OF INTRA-ABDOMINAL PRESSURE AND WOUND INFECTION IN THE POST-OPERATIVE PERIOD IN WOMEN WITH OBESITY - D. V. Marshalov; E. M. Shifman; I. A. Salov; A. P. Petrenko (Креативная хирургия и онкология, 2017)
To study the dependence of the wound infection rate after cesarean section and the level of postoperative intra-abdominal pressure (IAP) in obese patients. A study was conducted, involving 313 patients delivered by cesarean section. All patients were divided into 4 groups: control group 90, with degree I obesity 137, with II 49 and III 37 patients. The frequency of development of wound postoperative complications was determined, bacteriological studies of amniotic fluid, placenta, lousy and discharge wound of the anterior abdominal wall were carried out. Postoperative dynamics of IAP was investigated. IAP research was carried out using vesical indirect method. Wound postoperative complications were diagnosed in 17,9% of the puerperas, 8,6% of them had a discrepancy and suppuration of the sutures in the anterior abdominal wall. The incidence of wound complications increased with increasing severity of obesity. In patients with severe obesity, in the sowing of septic purulent wounds, microorganisms of the genus Escherichia coli, Enterococcus spp. prevailed. Analysis of postoperative dynamics of IAP showed that in obese patients its values exceeded those in the control group at all stages of the study. The correlation analysis showed the presence of a positive average force of communication between the postoperative intestinal paresis and the development of wound infection, r = 0,500 (p < 0,01). The relationship between wound infection and postoperative dynamics of IAP was approaching a strong-r ratio of 0,654 (p<0,001). Representatives of the intestinal microbioma are leading in patients with obesity in infection of the postoperative wound. In the contamination of the intestinal microflora, intra-abdominal hypertension (IAH) is one of the main triggers. Long-term persistent IAH in the postoperative period is a significant risk factor for the development of postoperative infectious complications.